Journal of Literary Theory (De Gruyter, 2007)
The Journal of Literary Theory is an international forum for debate in literary theory. It takes an interdisciplinary approach and is open to a broad variety of theories and methods, promoting their study, research, and development. JLT reaches out to disciplines dealing with theoretical foundations of the study of literature as well as to related fields of research such as musicology, art theory, and film studies as well as the sciences.